Manajemen Program Tahfidzul Quran Dalam Membentuk Karakter Peserta Didik Di SDIT Arruhul Jadid Jombang - Solechan, Solechan; Aulia, Rheizka (LP3M STIT Al Urwatul Wutsqo Jombang, 2023)
The purpose of this study is to describe the process of forming student character through the process of memorizing the Quran, as has been done in SDIT Ar-Ruhul Jadid Jombang. An educational institution that offers a tahfidz al-Qura'an program for its students. The existence of this program is an effort to shape the pious character of students in line with the values ??contained in the Qur'an so that it is expected to produce quality and moral graduates. In addition, a pious character can also fortify oneself from unfavorable Western cultural threats that can impact children's behavior. Therefore, this research must be made into a paper. This research uses qualitative methods, using techniques of data collection in the form of interviews, observation, and documentation. Furthermore, data analysis was carried out using descriptive and qualitative analysis. Research results show that the management of the Tahfidzul Qur'an program in shaping the character of students at SDIT ar-Ruhul Jadid begins with planning, organizing, implementing, and supervising, which are included in the series of program implementations. The process of character formation through the tahfidzul Qur'an program involves getting students used to always memorizing the Qur'an, especially when at school. Character building is also carried out by creating a school environment that has the nuances of the Qur'an. Through this process, the pious character of students is formed. The formation of pious character is in line with the school's vision, namely, students who have a righteous character